A study of urban form; its analysis and its implications for sustainable settlements in desert environments, with Walvis Bay as a case study - Munster, Detlev O (Department of Environmental and Geographical Science, 2023)
The purpose of this dissertation is to prove that there are urban forms that are appropriate to the desert environment, and that such forms together with basic design principles, can provide substantive design-oriented steps towards the environmental goal of sustainability in an urban context. The term "sustainability" has often been applied at a global level and is a holistic concept that tries to find solutions to a number of global issues. However, many of these problems are highly visible at an urban level, whereby the year 2000 over 50% of the world population is expected to manifest itself in urban areas. Sustainability therefore needs to be addressed at an urban level, a level which is closer to the people who both consume the most resources and produce the most waste. Among the many strategies available for addressing sustainability at a number of levels, sustainability as reflected in city design has played a small role. The stark reality that our living environments influence our daily activities and consumption patterns, and that these have been reflected in an unsustainable manner in many western settlements due to the physical layout of settlements, needs to be addressed. The planning system (with design as both a component· thereof and a result of the planning process) has a major role to play in addressing issues of sustainability from a physical perspective. Much research has been done on urban sustainability and urban form in the European context and is still developing. However, little research has been undertaken on the issues of urban sustainability in arid zones. Arid zones can be considered as the last frontiers of urban and rural expansion, and the prevailing trends of the last 30 years have indicated that these areas are experiencing rapid urbanisation. Due to extreme climatic conditions, it would be expected that these settlements. would develop within the constraints and opportunities such environments present. However, contemporary desert settlements have been founded on planning principles and standards adopted from other regions that are not arid in nature. This has resulted in settlements being inappropriate for their environments. Determining what is appropriate is rather difficult, especially from a physical perspective and could be perceived as very static. A proposition was therefore made to determine whether or not a sustainable urban form for desert environments existed, and whether there were specific design principles for desert settlements. This was intended to produce basic guidelines, which could then be used to facilitate discussion. The development of a coastal zone management plan (CZMP) for the Erongo region in Namibia, provided the opportunity to investigate the proposition. The CZMP required that a variety of issues (biophysical, infrastructural, legal, social, institutional, etc.) be investigated and presented in a baseline report. This baseline report highlighted a number of urban problems (such as urban sprawl, high infrastructural costs, and accessibility problems), which. need to be addressed by the coastal zone management plan. Walvis Bay, a settlement within the CZMP area, and a settlement in an arid zone (namely within the coastal area of the Namib Desert) proved to be an interesting case study, one that could be used to verify the proposition. Urban sustainability, urban morphology and urban design are discussed in detail in this dissertation, in order to present the theoretical tenets with which urban forms can be analysed, and from which an appropriate urban form can be developed for arid zones. Various tenets and principles of sustainability are addressed, and principles pertaining to sustainable design are outlined. Of notable significance is the fact that human design interacts with the natural world. A relationship can therefore be said to exist between the natural and human environments. Urban morphology is presented as a basis for illustrating that settlements develop from a number of influencing factors. Furthermore, the discussion of urban morphology also reveals the agendas which shape settlements, thereby giving certain settlements particular forms. The contempary debate between the respective merits of sprawling and compact settlements, raises a number of implications for sustainability. However, this dissertation proposes that the adoption of a compact settlement could achieve the means of sustainability better. The discussion of urban design emphasises the relationship between the built and natural environments, while at the same time presenting vital attributes that all settlements should either have or strive towards. Empirical research on urban settlements in the desert environments of Israel, Australia and the United States, and research on ancient and Arabic settlements in general, highlights design principles that could enhance the sustainability of settlements in desert environments. From many of the older settlements in the middle east, valuable lessons can be learnt regarding urban form in desert environments, lessons which are still applicable today. Walvis Bay's urban environment is analysed through an understanding of the basic performance dimensions inherent in urban forms, as well as urban form patterns and elements, sustainability principles and the vital attributes that urban environments should have. From this analysis, it becomes clear that certain urban forms are more suitable for desert environments, and that, as a consequence of an inappropriate urban form, Walvis Bay is unsustainable. By combining design principles of the Arabic settlements with aspects of a compact settlement, an appropriate urban form can be achieved. The attainment of a sustainable urban form (and one that encompasses the concept of "liveability") can be achieved for Walvis Bay, through the concrete suggestions made through this dissertation's analysis. This dissertation is a facilitating study, proceeding largely by a review of the existing literature on the subject. This "literature review", together with an analysis of Walvis Bay, is intended to present design principles for a sustainable urban form for desert environments.